Rewolucja 1989 roku w NRD - Kowalczuk, Ilko-Sascha (Pamięć i Sprawiedliwość, 2011)
The 1989 Revolution in the GDR Many factors — both domestic and those connected with the international situation — contributed to the fall of the communist system in the GDR. Crucial was the mood of the GDR society. At the end of the 1980s the people had had enough of the system. They were suffering from the economic crisis. The lack of perspectives and frustration triggered strong rebellious tendencies among the young. The Evangelical Church played a significant role in the shaping of such stances. In 1989 many priests and theologians took over the role of civil rights activists. The events in the GDR gathered momentum in May 1989. The dismantling of the fortified border between Austria and Hungary had more than a symbolic meaning. The Iron Curtain had been lifted for good. Thousands of East Germans tried to get to the FRG through Hungary or through Czechoslovakia and Poland. The FRG was an embodiment of the West they had been yearning for. The events accelerated in the fall. In Leipzig, demonstrations calling for freedom began after Monday masses. On 7 October, on the GDR founding anniver- sary, demonstrations of defiance were held in East Berlin and 50 other cities. The opposition, which had not been particularly numerous, consolidated and new formations were created. But most citizens waited to see what would happen. They expected reforms. Erich Honecker’s stepping down and Egon Krenz’s becoming the General Secretary of the Socialist Unity Party was insufficient. From the historical perspective the opening of the Berlin Wall on 9 November was a breakthrough forced by the societies of Poland, Hungary, Czechoslovakia and the GDR itself. In March 1990 a free election to the People’s Chamber (Volkskamer) was held. It was to guarantee democratic reforms. The next step was the unification of Germany. The 1989 and 1990 events in the GDR and other communist bloc countries were a form of a revolution. They did not, however, call for progress or strive for something entirely new. Their participants wanted to live in open societies, like the ones that seemed to exist in the Western democracies.